MAGNETIC RESONANCE IMAGING OF SKIN-COVERED BACK MASSES IN CHILDREN - VISRUTARATNA, Pannee; POOPAT, Punjama; SINGHAVECHSAKUL, Jesda; LIMPASTAN, Kriengsak (The ASEAN Journal of Radiology, 2023)
Purpose: To evaluate role of magnetic resonance imaging (MRI) in children with skin-covered back masses. Materials and methods: MR studies of fourteen children with skin-covered back masses were compared with surgical findings, histopathological reports, or clinical history. The greatest diameters of the palpable masses were compared with the greatest diameters of the masses on MR images. MRI findings important for treatment planning were noted. Results: The masses in five children were histologically proven; they were sacrococcygeal mature teratoma2 sacrococcygeal endodermal sinus tumor2 and Ewing sarcoma.1 Three children with lipomyelomeningocele, three with posterior meningocele, one with lipomyelocele, and one with anterior sacral meningocele had their masses surgically confirmed. The clinical history and MRI of the mass of one child were consistent with hemangioma. In the child with an anterior sacral meningocele, the greatest diameter of the mass on MR images was three times as big as that of the palpable mass. In three children (two with endodermal sinus tumor and one with Ewing sarcoma), the greatest diameters of the masses on MR images were twice as big as those of the palpable masses. Two children with endodermal sinus tumor and one with Ewing sarcoma had intraspinal invasion; one with a mature sacrococcygeal teratoma had a retrorectal extension; and one with an anterior sacral meningocele had a connection of the mass with the spinal canal. MRI findings of a child with hemangioma obviated biopsy. Conclusion: MRI had an important role in diagnosing these children and their treatment planning.